A variação estilística na concordância nominal e verbal como construção de identidade social - Salomão-Conchalo, Mircia Hermenegildo [UNESP] (2015)
Putting into question the theoretical status of the variable rule in the mid-80s, Eckert (2000) brought in a new trend in sociolinguistics when he proposed a new concept of variable rule, which now constitutes a privileged space of the construction of social language meaning. It is this theoretical model that this research adopted. Within this theoretical framework, the purpose of this study was to analyze the dynamics and social practices of two groups of students, ideologically opposed, from the same public school in the city of São José do Rio Preto. The variable processes of nominal and verbal agreement were analyzed as the identity construction of these social categories markers. In the survey, two groups of high school students, divided into two opposing social classes, called funkers and eclectics, were followed for two years in ethnographic research. On one hand, the group of funkers is formed by teenagers who do not give much value to their educational institution and who identify themselves with hip hop, funk and rap culture. On the other hand, members of the eclectic group, opposites ideologically, like going to school and doing extracurricular activities, such as language courses, and they have a greater focus on higher education in the future; furthermore, these students circulate among the other school groups and generally are able to live with the differences between them; it is for this reason they call themselves eclectics. The purpose of this research was to investigate how these students construct their linguistic and social identity through their social practices and their symbolic relationships. In order to follow these two communities of practice, the qualitative and quantitative research was adopted. The qualitative analysis was ethnographic and the research was characterized by a direct contact of the researcher with the investigated situation, in which relationships were established day by day ...